A Comparative Study of Phytochemical Profile of Different Solvents’ Effects on Total Phenolic Content and Antioxidant Activities of Various Parts of Halimium halimifolium - Sabah El gamouz; Omayma Bouzekri; Mostafa Elidrissi; Ali Amechrouq; M’bark Choukrad (Journal of Chemistry)
In the present work, the extraction and the variation of total phenolic and the flavonoid content of the Halimium halimifolium plant (the leaves and the stems) harvested from Morocco have been studied. It explores extracting the essential oil of this plant and analyzing its chemical composition by the gas chromatography-mass spectrometry (GC/MS). Interesting results have been obtained, in particular, the presence of 26 compounds where the major one is (+)-2-Bornanone (38.26%) followed by Eucalyptol (27.74%). This essential oil proves great antioxidant capacities which is measured with the total antioxidant activity (TAC) and the organic chemical compound 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays. On the other hand, using solvents with different polarities (the hexane, the dichloromethane, the ethyl acetate, the ethanol, and the water), the quantifying of the total phenolic and the flavonoid content for different crude extracts of the Halimium halimifolium was done. The results show simultaneous increasing in the total phenolic content of the crude extract and the solvent polarity.